Case Report: Low-Dose Decitabine Plus Anti-PD-1 Inhibitor Camrelizumab for Previously Treated Advanced Metastatic Non-Small Cell Lung Cancer - Yan, Xin; Zhao, Yongtian; Liu, Yang; Yang, Qingming; Dong, Liang; Wu, Zhiqiang; Nie, Jing; Chen, Deyun; Bai, Miaomiao; Ti, Dongdong; Feng, Kaichao; Han, Weidong (Frontiers in Oncology, 2020)
Background Although the programmed death 1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors have markedly changed the strategies of cancer treatment, most patients with advanced non-small cell lung cancer (NSCLC) do not respond to PD-1/PD-L1 monotherapy. Epigenetic drugs have been hypothesized to possess the potential to sensitize PD-1/PD-L1 inhibitors. Case presentation Three patients with advanced metastatic NSCLC failed to respond to first-line systemic therapy and had a low tumor mutation burden (TMB), low tumor neoantigen burden (TNB), low microsatellite instability(MSI), and HLA loss of heterozygosity (HLA LOH) according to their target lesion biopsies, all of which were considered unfavorable factors for PD-1/PD-L1 blockage. However, all three patients responded to low-dose decitabine, an epigenetic drug, in combination with camrelizumab (anti-PD-1 antibody), with only mild adverse events, indicating that low-dose decitabine can sensitize PD-1/PD-L1 inhibitors. Summary We report a novel therapy with low-dose decitabine plus camrelizumab (anti-PD-1 antibody) for advanced NSCLC on the basis of successful treatment of three patients, emphasizing the potential of epigenetic drugs to regulate PD-1/PD-L1 inhibitors in advanced NSCLC.